The STAT5 transcription factor in B-cells of patients with chronic lymphocytic leukemia - Matvieieva, A.S.; Kovalevska, L.M.; Ivanivska, T.S.; Klein, E.; Kashuba, E.V. (Вiopolymers and Cell, 2019)
Aim. To find out the cause of inhibition of the IL2-STAT5 signaling pathway in chronic lymphocytic leukemia (CLL) cells. Methods.CLL cells were isolated from peripheral blood, using gradient centrifugation on a ficoll-verografin mixture. Expression of the STAT1-6 genes at the mRNA level was analyzed, using the Oncomine database. Expression, phosphorylation status and cellular localization of the STAT5 protein were studied by fluorescence microscopy, using specific antibodies. Results.Unlike B-cells of healthy donors, expression of the STAT5A protein was low in the patient CLL cells. As we have previously shown, the IL-2-STAT5 (JAK-STAT5) signaling pathway is inhibited in CLL cells. Now we demonstrated a low level of phosphorylation of the STAT5 protein, or a complete lack of phosphorylation in CLL cells. The STAT5A protein shows cytoplasmic localization, indicating the absence of complexes in the nucleus that activate/repress transcription of the STAT5-dependent genes. Conclusions. Inhibition of the IL-2-STAT5 pathway in CLL cells is caused by a lack of the STAT5 proteins phosphorylation and/or the absence of the active STAT5A transcription complexes in the nucleus of CLL cells. Мета. Встановити причину блокування сигнального шляху IL2-STAT5 у клітинах крові хворих на хронічний ліфмолейкоз (ХЛЛ). Методи. Клітини ХЛЛ виділяли з периферичної крові пацієнтів, хворих на ХЛЛ, за допомогою центрифугування у градієнтіфікол-верографін. Експресію генів STAT1-6 на рівні мРНК аналізували за допомогою бази даних Oncomine. Експресію, статус фосфорилювання і клітинну локалізацію білка STAT5 вивчали методом флуоресцентної мікроскопії з використаннім специфічних антитіл. Результати. Навідмінувід В-клітин здорових людей, експресія білка STAT5А була низькою у клітинах хворих на ХЛЛ. Як нами було встановлено раніше, сигнальний шлях IL-2-STAT5 (JAK-STAT5) інгібовано у клітинах ХЛЛ. Нами було показано низький рівень фосфорилювання білків STAT5, або повну відсутність фосфорильованої форми протеїнів в лейкемічних клітинах. Протеїн STAT5А показує цитоплазматичну локалізацію, що вказує н авідсутність у ядрікомплексів, активуючих транскрипцію генів, залежних від фактора транскрипції STAT5. Висновки. Інгибування сигнального клітинного шляху IL-2-STAT5 в клітинах крові хворих на ХЛЛ реалізується за рахунок гіпофосфорилювання протеїнів STAT5 та/або відсутності активних комплексів транскрипції STAT5А у ядрі лейкемичних клітин. Цель. Установить причину блокирования сигнального пути IL2-STAT5 в клетках крови больных хроническим лимфолейкозом (ХЛЛ). Методы. Лейкемические клетки выделяли из периферической крови с помощью центрифугирования в градиенте плотности фиколл-верографин. Экспрессию генов STAT1-6 на уровне мРНК анализировали с помощью базы данных Oncomine. Экспрессию, статус фосфорилирования и клеточную локализацию белка STAT5 изучали методом флуоресцентной микроскопии с использованием специфических антител. Результаты. В отличие от В-клеток здоровых людей, экспрессия белка STAT5А была низкой в клетках больных ХЛЛ. Как нами было установлено ранее, сигнальный путь IL-2-STAT5 (JAK-STAT5) ингибирован в клетках ХЛЛ. Намибылпоказаннизкийуровеньфосфорилированиябелков STAT5 или полное отсутствие фосфорилированной формы протеинов в лейкемических клетках. Протеин STAT5А показывает цитоплазматическую локализацию, что указывает на отсутствие в ядре комплексов, активирующих транскрипцию генов, зависимых от фактора транскрипции STAT5. Выводы. Ингибирование сигнального клеточного пути IL-2-STAT5 в клетках крови больных ХЛЛ происходит за счёт гипофосфорилирования белков STAT5 и/или отсутствия активных комплексов транскрипции STAT5А в ядре лейкемических клеток.